LncRNA NEAT1 acts as a key regulator of cell apoptosis and inflammatory response by the miR-944/TRIM37 axis in acute lung injury - Cheng Chen; Haitao Zhang; Min Ge; Jiaxin Ye; Ruisha Li; Dongjin Wang (Journal of Pharmacological Sciences, 2021)
Acute lung injury (ALI), a common complication of sepsis, is characterized by the impairment and injury of pulmonary function. The nuclear factor kappa-B (NF-κB) pathway is activated in ALI. Tripartite motif-containing 37 (TRIM37) can activate the NF-κB pathway and is closely associated with inflammation. The purpose of our study is to reveal the role of TRIM37 in ALI. The present study revealed that TRIM37 presented high levels in lung tissues of ALI mice, and knockdown of TRIM37 alleviated lipopolysaccharide (LPS)-induced lung injury, inflammatory response, and cell apoptosis in vivo. In addition, knockdown of TRIM37 inhibited the inflammatory response, and cell apoptosis of LPS-treated WI-38 cells. Mechanistically, miR-944 was identified to bind with and negatively regulate TRIM37. Furthermore, NEAT1 was indicated to act as a competitive endogenous RNA to promote TRIM37 expression by sequestering miR-944. Detailly, NEAT1 bound with miR-944, negatively modulated miR-944 expression, and positively modulated TRIM37 expression. The rescue assays suggested that overexpression of TRIM37 rescued the influence of NEAT1 knockdown on cell apoptosis and inflammatory response. Overall, NEAT1 facilitated cell apoptosis and inflammatory response of WI-38 cells by the miR-944/TRIM37 axis in sepsis-induced ALI, implying that NEAT1 may provide a novel insight for the treatment of sepsis-induced ALI.